Development and evaluation of a pH-sensitive, naturally crosslinked alginate-chitosan hydrogel for drug delivery applications - Khatibi, Negin; Naimi-Jamal, M. Reza; Balalaie, Saeed; Shokoohmand, Ali (Frontiers in Biomaterials Science, 2024)
The development of safe and efficient delivery systems for targeted and controlled release of therapeutic agents has become a major focus in pharmacotherapy. The colon is one organ that serves as an optimal site for the absorption of protein and peptide drugs, offering significant potential for both localized and systemic therapies. However, effective drug delivery is challenged by the need to protect these drugs from premature absorption and maintain their stability across the varying pH levels of the gastrointestinal tract. In this study, we introduce, for the first time, a fully natural hydrogel system composed of N-acetylated chitosan and alginate, crosslinked using a phenylalaninephenylalanine dipeptide. The hydrogel demonstrates a unique swelling behavior, allowing for a solvent-free drug-loading method and pH-sensitive release properties. In a colon-simulated pH environment, the hydrogel achieved a high drug release efficiency, with 77.6% of the tested drug sulfasalazine and 51% of hydrocortisone over five hours. These findings underscore hydrogel's potential as a promising drug delivery carrier for targeted gastrointestinal treatments, with the capacity to enhance the efficacy of current therapeutic options.